Analisis Rasio Perputaran dan Periode Rata-Rata Pengumpulan Piutang Sebagai Dasar Penilaian Efektivitas Kebijakan Kredit PT. ISAM - Ervina Inayah Zulna; Ira Novianty; Hastuti Hastuti (Indonesian Accounting Literacy Journal, 2023)
Company management needs to implement appropriate policies in order to increase company value and reach the goals. The main activity of PT. ISAM to achieve the goal is sales transactions, especially credit sales. The risk of credit sales is uncollectible receivable, so receivable control and management is needed to minimize the risk of company losses. Therefore, an effective credit policy must be implemented. The purpose of this research is to evaluate the effectiveness of PT. ISAM credit policy by comparing the analysis of the receivables turnover ratio and the average collection period with the standards policies of PT. ISAM. Receivable turnover and the average collection period of PT. ISAM has not reached the standard, which is 12 times and 30 days. So that the credit policy has not been effective. It is influenced by the low level of sales so that the receivables turnover and the average collection period are not optimal.